Produtividade da indústria brasileira de transformação: uma abordagem setorial utilizando a teoria da fronteira estocástica - Lima, Adalberto de (2001)
This work anylises the changes of productivity and technical efficience for the brazilian transformation industries between 1985 and 1996. For this analysis was used the theory of Stochastic Frontier to measure technical efficiency and Malmquist index to mesure productivity. Moreover, there are an analysis about the influence of Opness and the long term loans from BNDES over the Total Factor Productivity of brasiliam industries. The Malmquist index, shows that the productivity gains was caused by the change of technical efficiency indeed the technical change. At least, none ofthe 13 industriaIs sectors shifted de productivity frontier of brasilian industy.